2014
DOI: 10.12681/mms.777
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic bryozoan community of Posidonia oceanica (L.) Delile leaves in two different meadows at disturbed and control locations

Abstract: The impact of fish farming activities on Posidonia oceanica meadows in the Aegean Sea have been detected using bryozoan epiphytes as indicators of disturbance. Samples were collected by SCUBA diving in September 2004 in order to compare assemblages between disturbed (I1:0-5 m; I2:5-10 m and I3:10-15 m) and control meadows (C1:0-5 m; C2:5-10 m and C3:10-15 m) located at different depths. Regarding the mean percentage coverage of bryozoans, significant differences were found between stations, leaf sides, depths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…Monoporella bouchardii is a common bryozoan species in Lebanon, the Greek islands Turkey, and Egypt (Harmelin, 2014). It was found in cavities of rocky bottoms, on Posidonia rhizomes, and on leaves in Turkey (Nicoletti et al, 1995;Kocak and Aydin-Onen, 2014). In these studies, specimens collected from Yenikaş and Engeceli Bay (İzmir) was assigned to M. nodulifera.…”
Section: Resultsmentioning
confidence: 99%
“…Monoporella bouchardii is a common bryozoan species in Lebanon, the Greek islands Turkey, and Egypt (Harmelin, 2014). It was found in cavities of rocky bottoms, on Posidonia rhizomes, and on leaves in Turkey (Nicoletti et al, 1995;Kocak and Aydin-Onen, 2014). In these studies, specimens collected from Yenikaş and Engeceli Bay (İzmir) was assigned to M. nodulifera.…”
Section: Resultsmentioning
confidence: 99%
“…This character is significant for differentiating between the present species and a similar species (N. stipata Gosse, 1855) in which the proximal portions of autozooids taper and lack basal dilatations. Additionally, peristomial length may be used to distinguish between these two species: Distribution and Habitat: Nolella dilatata had been recorded from both the western basin of the Mediterranean (Hayward and McKinney, 2002;Souto et al, 2010Souto et al, , 2014Ben Ismail et al, 2012) and the eastern basin (d 0 Hondt, 1988a;Morri et al, 1999;Koc¸ak et al, 2002;Koc¸ak and Aydin-onen, 2014). Nevertheless; Souto et al (2014) indicated that the real distribution of European Nolella species is uncertain due to the uncertain status of the species, and that Nolella gigantea (Busk, 1856) may be a synonym of N. stipata.…”
Section: Resultsmentioning
confidence: 99%
“…Berdasarkan hal tersebut, perifiton memegang peranan yang sangat penting dalam struktur trofik pada ekosistem lamun. Selain itu, perifiton juga dijadikan sebagai bioindikator pencemaran karena dapat merespon perubahan lingkungan perairan (Indrawati et al, 2010 ;Junda et al, 2013 ;Kocak and Onen, 2014 ;Fitriani dan Maulana, 2015).…”
Section: Pendahuluanunclassified